Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran Pendidikan Pancasila Menggunakan Model Cooperative Learning Tipe Course Review Horray di Kelas IV SDN 101100 Gunung Tua Kabupaten Padang Lawas Utara - Putri, Siti Gahara; Waldi, Atri; Anita, Yesi; Iraqi, Hana Shilfia (Darul Yasin Al Sys, 2025)
This study aims to improve student learning outcomes in Pancasila Education learning in class IV SDN 101100 Gunung Tua, North Padang Lawas Regency by using the Cooperative Learning learning model of the Course Review Horray (CRH) type. This study is a Classroom Action Research (CAR) which is carried out in two cycles, each consisting of the planning, implementation, observation, and reflection stages. The subjects of this study were 23 class IV students. Data were collected through assessment of teaching modules, implementation processes and learning outcomes. The results showed that the application of the CRH learning model was able to improve student learning outcomes. In cycle I, the teaching module aspect obtained an average of 87% (B) increasing in cycle II to 92% (SB). While in the teacher aspect, it obtained an average of 82% (B) and increased in cycle II to 93% (SB). In the student aspect, it obtained an average of 82% (B) increasing in cycle II to 93% (SB). And the learning outcomes of cycle I obtained an average of 77% (C), increasing in cycle II to 84% (B). It can be concluded that the Cooperative Learning model of the Course Review Horray type can improve student learning outcomes in Pancasila Education learning.